The Potential Effects of Sea-Level Rise on Florida’s Coastal Ecosystems - Whitney Gray (EDIS)
Sea-level rise may have significant effects on Florida’s coastal ecosystems. These ecosystems are the foundation upon which much of Florida’s natural beauty and economy are based. Understanding what changes may happen in the future can help us plan for those changes and, to the extent possible, lessen the impacts of those changes. This 5-page fact sheet was written by Whitney Gray, and published by the UF Department of Sea Grant, October 2013.